2013
DOI: 10.3892/ijo.2013.1798
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of gene expression in vestibular schwannomas reveals SPP1/MET signaling pathway and androgen receptor deregulation

Abstract: Vestibular schwannomas are benign neoplasms that arise from the vestibular nerve. The hallmark of these tumors is the biallelic inactivation of neurofibromin 2 (NF2). Transcriptomic alterations, such as the neuregulin 1 (NRG1)/ErbB2 pathway, have been described in schwannomas. In this study, we performed a whole transcriptome analysis in 31 vestibular schwannomas and 9 control nerves in the Affymetrix Gene 1.0 ST platform, validated by quantitative real-time PCR (qRT-PCR) using TaqMan Low Density arrays. We pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(72 citation statements)
references
References 80 publications
6
65
1
Order By: Relevance
“…Prior to this study, there was only one comparative analysis between meningioma and schwannoma at the genomic level reported in the literature (Torres-Martin et al, 2013b, Torres-Martin et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Prior to this study, there was only one comparative analysis between meningioma and schwannoma at the genomic level reported in the literature (Torres-Martin et al, 2013b, Torres-Martin et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an independent study analyzing 31 schwannomas revealed no clear distinctions of germline and sporadic schwannomas. 36 Given the observation that sporadic VS tissue harbors 60%-100% inactivation of NF2, it is very likely that the molecular pathogenesis of both sporadic and germline schwannomas is similar. 13,34 Targeted therapeutics and rational drug targeting strategies are of great interest in the treatment of schwannoma and other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway profiling showed that DNA damage response (DDR) and cell death were among the top 10 pathways enriched with the DKO_Liver_Reversed gene set (Figure S4B). Interestingly, GSEA showed this set of genes also significantly associated with genes upregulated in human vestibular schwannomas (VS) (Torres-Martin et al, 2013) despite the tissue and cell type differences (Figure S4C), implying their potential relevance to NF2.…”
Section: Inactivation Of Nf2 Induced P53 Expression and Dna Damage Chmentioning
confidence: 99%
“…We postulated that a p53-mediated DNA damage/senescence program might also constrict the growth of human NF2 tumors. To test this hypothesis, we conducted GSEA with our HSGS on three published human schwannomas and meningiomas microarray datasets (Clark et al, 2013; Tabernero et al, 2009; Torres-Martin et al, 2013). Despite the difference in cell types, we observed significant enrichment of the Hepatocyte_Senescence_Up gene set among genes upregulated in NF2-associated schwannomas compared to normal nerves or in NF2-associated meningiomas (NF2) compared to meningiomas that do not contain NF2 mutations (nonNF2) (Figure 6A).…”
Section: Inactivation Of Nf2 Induced P53 Expression and Dna Damage Chmentioning
confidence: 99%